2020
DOI: 10.5178/lebs.2020.76
|View full text |Cite
|
Sign up to set email alerts
|

Preference for Anonymous Giving

Abstract: Individuals sometimes prefer to anonymously donate money when they can publicly do so. In other words, they deliberately hide their costly prosocial behavior from a broad audience. While existing research has collated various evolutionary theories emphasizing the value of public prosocial behavior, it has not endeavored to address the preference for anonymous giving. The article discussed potential explanations for the preference and pointed to the importance of further scholarly discussion about the value and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In this paper, however, donors themselves could choose to be non-anonymous or anonymous on an online sequential donation platform, which means that they had the option to hide their name and avatar or not. Past studies based on these similar anonymous behaviors point out that the most common reason driving people to donate anonymously was to avoid judgments from the public (Peacey and Sanders, 2013 ; Raihani, 2014 ; Imada, 2020 ; Raihani and Power, 2021 ).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…In this paper, however, donors themselves could choose to be non-anonymous or anonymous on an online sequential donation platform, which means that they had the option to hide their name and avatar or not. Past studies based on these similar anonymous behaviors point out that the most common reason driving people to donate anonymously was to avoid judgments from the public (Peacey and Sanders, 2013 ; Raihani, 2014 ; Imada, 2020 ; Raihani and Power, 2021 ).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Experimental studies have shown that individuals feel uncomfortable when they learn that they are morally superior to their peers (Cowgill, 2017 ) or when their moral actions are highlighted to others (Wang & Tong, 2015 ) and these negative feelings might prompt individuals to hide their good deeds from others. For instance, when making charitable donations online, people often hide their donations from others by making them anonymously ( Big Charitable Gifts , 2020 ; Imada, 2020 ) and the tendency to donate anonymously (either by hiding their name or the amount donated) is higher when the donation is especially generous (Mokos & Scheuring, 2019 ; Peacey & Sanders, 2014 ; Raihani, 2014 ). Similar results have been obtained in experimental settings (Jones & Linardi, 2014 ), although we note that most of these studies involve WEIRD (Henrich et al, 2010 ) populations and it remains an open question as to whether these patterns would generalise to different cultures.…”
Section: Reputation Management Strategies In Humansmentioning
confidence: 99%
“…Experimental studies have shown that individuals feel uncomfortable when they learn that they are morally superior to their peers (169) or when their moral actions are highlighted to others (170) and these negative feelings might prompt individuals to hide their good deeds from others. For instance, when making charitable donations online, people often hide their donations from others by making them anonymously (171,172) and the tendency to donate anonymously (either by hiding their name or the amount donated) is higher when the donation is especially generous (173)(174)(175). Similar results have been obtained in experimental settings (176), though we note that most of these studies involve WEIRD (177) populations and it remains an open question as to whether these patterns would generalise to different cultures.…”
Section: Reputation Management Strategies In Humansmentioning
confidence: 99%